A Survey to Identify Screen Test Usage by Certified Orthoptists Across the United States of America. Issue 2 (3rd April 2023) - Attzs, Michelle S.; Christoff, Alex
ABSTRACT: Purpose: To ascertain the use of screen tests for assessing strabismus under binocular viewing conditions by certified orthoptist colleagues around the United States of America. Methods: A link to an online survey was distributed to all 440 registered members of the American Association of Certified Orthoptists in early 2022. A total of 135 certified orthoptists responded. Results: Of the 135 respondents, 51% were from a public practice, 36% were private practice and 13% from a mixture of both. A large proportion of respondents did not use binocular screen tests to measure strabismus such as the Lancaster red/green test (85%) or Hess screen test (93%), although one respondent reported using the Harms screen test. Most respondents reported using single or double Maddox rods (75%), synoptophore (44%) and prisms (14%) in their practice to quantify strabismus clinically. Conclusion: There is limited use of screen tests in private and public practice in the USA. The ergonomic requirements of such tests are prohibitive to their implementation in modern clinical practice.